Optimal xylanase production using Penicilium janthinellum NCIM 1169: a model based approach - Meshram, Mukesh; Kulkarni, Abhijit; Jayaraman, Valadi K.; Kulkarni, B. D.; Lele, S. S. (Biochemical Engineering Journal, 2008)
Xylanases are an industrially important class of hydrolytic enzymes that degrade xylans. Production of xylanase from a fungal culture by submerged fermentation and optimization of the operating conditions for maximum activity are the two aims of the present study. Penicillium janthinellum NCIM 1169 with Mandels-Weber medium, sugarcane bagassse (40#) as a carbon source and beef extract as a nitrogen source were used in the experiments. We did 41 experiments to see the effect of variations in carbon, nitrogen source, pH, and inoculum on xylanase activity. This data was then used to build an input/output model using multiple linear regression, back propagation neural network and lazy learning algorithm. It was found that lazy learning model correlated well in mapping input/output data. This model was then utilized as an objective function in genetic algorithm to find the optimal combination of the operating conditions to get the maximum xylanase activity. It was observed that with carbon source, 1.63%, nitrogen source, 0.16%, pH, 4.1, and inoculum, 5.5%, maximum xylanase activity of 28.98 +/- 1.73 U/ml was achieved. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Artificial intelligence; Enzyme activity; Fermentation; Modeling; Optimization; Xylanase

Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Navigating the challenges of engineering composite specialized metabolite pathways in plants - Gharat, Sachin A.; Tamhane, Vaijayanti A.; Giri, Ashok P.; Aharoni, Asaph (Plant Journal, 2025)
Plants are a valuable source of diverse specialized metabolites with numerous applications. However, these compounds are often produced in limited quantities, particularly under unfavorable ecological conditions. To achieve sufficient levels of target metabolites, alternative strategies such as pathway engineering in heterologous systems like microbes (e.g., bacteria and fungi) or cell-free systems can be employed. Another approach is plant engineering, which aims to either enhance the native production in the original plant or reconstruct the target pathway in a model plant system. Although increasing metabolite production in the native plant is a promising strategy, these source plants are often exotic and pose significant challenges for genetic manipulation. Effective pathway engineering requires comprehensive prior knowledge of the genes and enzymes involved, as well as the precursor, intermediate, branching, and final metabolites. Thus, a thorough elucidation of the biosynthetic pathway is closely linked to successful metabolic engineering in host or model systems. In this review, we highlight recent advances in strategies for biosynthetic pathway elucidation and metabolic engineering. We focus on efforts to engineer complex, multi-step pathways that require the expression of at least eight genes for transient and three genes for stable transformation. Reports on the engineering of complex pathways in stably transformed plants remain relatively scarce. We discuss the major hurdles in pathway elucidation and strategies for overcoming them, followed by an overview of achievements, challenges, and solutions in pathway reconstitution through metabolic engineering. Recent advances including computer-based predictions offer valuable platforms for the sustainable production of specialized metabolites in plants.
Keywords: Biosynthetic pathway; Enzyme activity; Gene expression; Metabolic engineering; Metabolites